2013
DOI: 10.3390/md11082882
|View full text |Cite
|
Sign up to set email alerts
|

Separacenes A–D, Novel Polyene Polyols from the Marine Actinomycete, Streptomyces sp.

Abstract: Separacenes A–D (1–4), novel polyene polyols, were isolated from Streptomyces sp. collected from the southern area of Jeju Island, Korea. The chemical structures of 1–4 were established by NMR, mass, UV, and IR spectroscopy as well as the modified Mosher’s method. Separacenes A–B (1–2), which share an identical planar structure but possess different relative configurations, bear tetraene units flanked by two diol moieties, whereas the stereoisomeric separacenes C–D (3–4) possess a triene moiety between two dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Furthermore, the UV–Vis spectrum associated with these compounds was suggestive of a tetraene moiety in each, due to the typical absorption band from 280 to 340 nm with a clear maxima at 312 nm (Supplementary material). Taken together, these data suggest the presence of tetraene polyols in the extract, which would be in-line with the production of PKS or hybrid PKS natural products by similar actinomycetes such as the novonestmycins, separacenes, bahamaolides and marinisporolides (Kwon et al 2009 ; Kim et al 2012 ; Bae et al 2013 ; Wan et al 2015 ). However, the parent masses observed in this study were not found to correlate with any known molecules of this class in the MarinLit or Dictionary of Natural Products databases.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, the UV–Vis spectrum associated with these compounds was suggestive of a tetraene moiety in each, due to the typical absorption band from 280 to 340 nm with a clear maxima at 312 nm (Supplementary material). Taken together, these data suggest the presence of tetraene polyols in the extract, which would be in-line with the production of PKS or hybrid PKS natural products by similar actinomycetes such as the novonestmycins, separacenes, bahamaolides and marinisporolides (Kwon et al 2009 ; Kim et al 2012 ; Bae et al 2013 ; Wan et al 2015 ). However, the parent masses observed in this study were not found to correlate with any known molecules of this class in the MarinLit or Dictionary of Natural Products databases.…”
Section: Discussionsupporting
confidence: 56%
“…The toxicity of polyenes against mammalian cells is well documented in polyenic antibiotics (Bolard, 1986), and cytotoxicity is observed even in polyene molecules harbouring only four conjugated double bonds (Bae et al ., 2013). The formation of polyene–lipid complexes can lead to changes in membrane permeability, resulting in haemolysis and cytolysis (Hsuchen & Feingold, 1973; Siegel, 1977; Brajtburg et al ., 1980; Bolard, 1986; Aparicio et al ., 2004).…”
Section: Gbs Pigment and Haemolysin Identical Or Nonidentical Twins?mentioning
confidence: 99%
“…Polyenes display a high affinity to sterols and phospholipids of the cell membrane, and they are haemolytic as well as cytolytic (Bolard, 1986;Knopik-Skrocka & Bielawski, 2002;Aparicio et al, 2004;Knopik-Skrocka et al, 2007). The toxicity of polyenes against mammalian cells is well documented in polyenic antibiotics (Bolard, 1986), and cytotoxicity is observed even in polyene molecules harbouring only four conjugated double bonds (Bae et al, 2013). The formation of polyene-lipid complexes can lead to changes in membrane permeability, resulting in haemolysis and cytolysis (Hsuchen & Feingold, 1973;Siegel, 1977;Brajtburg et al, 1980;Bolard, 1986;Aparicio et al, 2004).…”
Section: Gbs Pigment and Haemolysin Identical Or Nonidentical Twins?mentioning
confidence: 99%
“…HN001, isolated from a fresh branch of the mangrove plant Sonneratia ovata , had led to the isolation and characterization of four new polyketides: nectriacid A ( 1 ), nectriacid B ( 2 ), nectriacid C ( 3 ), and 12-epicitreoisocoumarinol ( 4 ), as well as three known compounds: citreoisocoumarinol ( 5 ), citreoisocoumarin ( 6 ), and macrocarpon C ( 7 ) ( Figure 1 ). Previous studies showed that linear polyene derivatives exhibited anti-inflammatory [ 13 ], antihypertensive [ 14 ], antibacterial [ 15 ], and antifungal activities [ 16 ]. In this report, compounds ( 1 – 7 ) from the Nectria sp.…”
Section: Introductionmentioning
confidence: 99%